Porous Structure Evolution of Cellulose Carbon Fibres during Oxidation in Carbon Dioxide - Krzysztof Babeł (Adsorption Science & Technology)
The isothermal oxidation of regenerated cellulose carbon fibres in the presence of CO 2 or steam was described, together with the changes in the porous structures of the active fibres that evolve during different stages of the process. Three such stages were defined. In the initial stage of heating and out-gassing, changes in the porous structure were related to the violent pyrolysis that occurred. As a result, a considerable number of micropores (accessible to nitrogen) were generated together with a small number of mesopores. The next stage (principal activation stage) involved burning at a constant rate accompanied by an uniform increase in the micropore volume. In the third stage, an increased rate of oxidation was observed. This was accompanied by the development of transitional pores linked with the simultaneous limitation of micropore evolution. This stage was not efficient.